Dampak Pembiayaan Mikro Syariah Dalam Meningkatkan Pendapatan Usaha Kecil Pada PT. BPRS Mitra Agro Usaha - Zulaiha, Erni; Albab, Ulil; Ruslaini (CV. ULIL ALBAB CORP, 2024)
This research aims to evaluate the impact of Islamic microfinance distributed by PT. BPRS Mitra Agro Usaha on the income growth of small businesses. As a sharia-compliant financial institution focusing on SMEs, PT. BPRS Mitra Agro Usaha provides access to sharia-based financing for small business owners to expand and develop their businesses. This research uses qualitative and descriptive methods, focusing on the analysis of impacts on income, production capacity, distribution, and innovation after receiving financing.The research results indicate that Islamic microfinance received by small business owners significantly contributes to increasing income, expanding production capacity, and enhancing competitiveness through innovation. However, this research also reveals several challenges faced by PT. BPRS Mitra Agro Usaha, such as non-performing financing (NPF) risk and suboptimal financial management among business owners. To address these challenges, PT. BPRS Mitra Agro Usaha needs to improve risk assessment systems, strengthen digital services, and provide financial education for business owners.By overcoming these challenges, PT. BPRS Mitra Agro Usaha is expected to support the growth and development of SMEs in Indonesia through more effective and sustainable Islamic microfinance. The results of this research are expected to serve as a basis for developing better sharia financing policies to support local and national economic growth.